2002
DOI: 10.1354/vp.39-3-293
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Rodent Models of Brainstem Tumors

Abstract: Abstract. Despite recent advances in surgical technology, resection is not an option for many brainstem tumors. Experimental models have played essential roles in examining new approaches to therapy. The objective of the present study was to generate models by determining coordinates for safe inoculation into the brainstem of mice and rats, and to establish whether the implantation of heterotopic cells would create reproducible survival curves. Morbidity and survival studies were used to map stereotactic coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The brainstem glioma model was modified from the one as previously described [27,40]. The animals were anesthetized with ketamine (40mg/Kg) in combination with xylazine (10mg/Kg) administered intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
“…The brainstem glioma model was modified from the one as previously described [27,40]. The animals were anesthetized with ketamine (40mg/Kg) in combination with xylazine (10mg/Kg) administered intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
“…4). 56,57,65,123 Wu et al 122 demonstrated that carboplatin could be locally delivered to neoplastic cells in a rat brainstem tumor model with mini-osmotic pumps, which resulted in a prolongation of survival. Moreover, Lonser et al 71 documented the safety of locally infused Gd-bound albumin via stereotactically implanted cannulas into large areas of the primate midbrain and pons, followed by other reports showing the safety of CED of chemotherapeutic agents, such as gemcitabine and carboplatin, infused into the primate brainstem, although dose-dependent toxicity has been found with carboplatin.…”
Section: New Therapeutic Perspective Strategiesmentioning
confidence: 99%
“…We observed significant morbidity in rats infused at 5 l/h for 7 days (8) but recognize that morbidity in rodent studies depends on the volume and site of the infusion (37). Recent studies have shown that 4 l of solution can be infused into the rat brainstem at rates of 30 l/h (33).…”
Section: Discussionmentioning
confidence: 95%